2011
DOI: 10.1038/emboj.2011.301
|View full text |Cite
|
Sign up to set email alerts
|

CAMTA1 is a novel tumour suppressor regulated by miR-9/9*in glioblastoma stem cells

Abstract: Cancer stem cells or cancer initiating cells are believed to contribute to cancer recurrence after therapy. MicroRNAs (miRNAs) are short RNA molecules with fundamental roles in gene regulation. The role of miRNAs in cancer stem cells is only poorly understood. Here, we report miRNA expression profiles of glioblastoma stem cell-containing CD133(+) cell populations. We find that miR-9, miR-9(*) (referred to as miR-9/9(*)), miR-17 and miR-106b are highly abundant in CD133(+) cells. Furthermore, inhibition of miR-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
120
1
6

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 148 publications
(131 citation statements)
references
References 72 publications
4
120
1
6
Order By: Relevance
“…One of the transcripts of mir-4670-5p is calmodulin-binding transcription activator 1 (CAMTA1). Because the previous studies showed that CAMTA1 inhibits tumor progression in some cancers [21,27], the excessive mir-4670-5p in tumor cells due to the interaction with platelets may inhibit the expression of CAMTA1 and lead to the progression of tumor cells. However, to our knowledge, there are no reports demonstrating the significance of mir-4670-5p in cancer cells, and thus further investigation is needed to elucidate its function.…”
Section: Discussionmentioning
confidence: 99%
“…One of the transcripts of mir-4670-5p is calmodulin-binding transcription activator 1 (CAMTA1). Because the previous studies showed that CAMTA1 inhibits tumor progression in some cancers [21,27], the excessive mir-4670-5p in tumor cells due to the interaction with platelets may inhibit the expression of CAMTA1 and lead to the progression of tumor cells. However, to our knowledge, there are no reports demonstrating the significance of mir-4670-5p in cancer cells, and thus further investigation is needed to elucidate its function.…”
Section: Discussionmentioning
confidence: 99%
“…suppressor within neurons and glial cells (10,11), we never observed any tumors in CAMTA1-KO mice before death.…”
Section: Significancementioning
confidence: 89%
“…The mechanistic basis of these abnormalities has not been defined. CAMTA1 also has been implicated as a tumor suppressor in neuroblastoma and glioblastoma (10,11).…”
mentioning
confidence: 99%
“…À l'inverse, une forte expression de miR-9 a été associée à une sous-classe de glioblastomes, une forme fréquente et agressive de tumeurs cérébrales chez l'adulte [33]. Dans ce contexte, l'expression de miR-9/9* apparaît réguler, au sein de la masse tumorale, les propriétés de certaines cellules appelées cellules souches cancéreuses [34,35]. Ces cellules, qui ont un fort potentiel d'autorenouvellement à long terme, sont également plus résistantes à la chimiothérapie et sont ainsi considérées comme probablement responsables des rechutes [36].…”
Section: Mir-9 Et Les Progéniteurs Neuraux En Contexte Pathologiqueunclassified
“…Ces cellules, qui ont un fort potentiel d'autorenouvellement à long terme, sont également plus résistantes à la chimiothérapie et sont ainsi considérées comme probablement responsables des rechutes [36]. Une étude montre que, dans les glioblastomes, ces cellules souches expriment un plus fort niveau de miR-9/9* [34]. L'expression de miR-9/9* dans ces cellules est nécessaire à leur capacité à s'autorenouveler sur de longues durées en culture.…”
Section: Mir-9 Et Les Progéniteurs Neuraux En Contexte Pathologiqueunclassified